Chromosomal divergence and evolutionary inferences in Pentatomomorpha infraorder (Hemiptera, Heteroptera) based on the chromosomal location of ribosomal genes - Souza-Firmino, Tatiani Seni de [UNESP]; Chaboli Alevi, Kaio Cesar [UNESP]; Itoyama, Mary Massumi [UNESP] (Public Library Science, 2020)
With the objective of assisting in the understanding of the chromosome evolution of Pentatomomorpha and in the quest to understand how the genome organizes/reorganizes for the chromosomal position of the 45S rDNA in this infraorder, we analyzed 15 species (it has being 12 never studied before by FISH) of Pentatomomorpha with the probe of 18S rDNA. The mapping of the 45S gene in the Coreidae family demonstrated that the species presented markings on the autosomes, with the exception of Acanthocephala parensis and Leptoglossus gonagra that showed markers on m-chromosomes. Most species of the Pentatomidae family showed marking in the autosomes, except for two species that had 45S rDNA on X sex chromosome (Odmalea sp. and Graphosoma lineatum) and two that showed marking on the X and Y sex chromosomes. Species of the Pyrrhocoridae family showed 18S rDNA markers in autosomes, X chromosome as well as in Neo X. The Largidae and Scutelleridae families were represented by only one species that showed marking on the X sex chromosome and on a pair of autosomes, respectively. Based on this, we characterized the arrangement of 45S DNAr in the chromosomes of 12 new species of Heteroptera and discussed the main evolutionary events related to the genomic reorganization of these species during the events of chromosome and karyotype evolution in Pentatomomorpha infraorder.